2013
DOI: 10.1007/s00592-013-0479-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of human islets in a subject at onset of type 1 diabetes

Abstract: Swollen islet cells have been repeatedly described at onset of type 1 diabetes, but the underlying mechanism of this observation, termed hydropic degeneration, awaits characterization. In this study, laser capture microdissection was applied to extract the islets from an organ donor that died at onset of type 1 diabetes and from an organ donor without pancreatic disease. Morphologic analysis revealed extensive hydropic degeneration in 73% of the islets from the donor with type 1 diabetes. Expression levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…In contrast, we observed inhibition of pathways that use glucose for other purposes, such as the synthesis of glycosaminoglycans. These observations concur with the outcome of another study, where gene expression analysis in pancreatic islets from T1D patients showed not only up-regulation of genes involved in cell death, but significant inhibition of glucose transport as well 3 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, we observed inhibition of pathways that use glucose for other purposes, such as the synthesis of glycosaminoglycans. These observations concur with the outcome of another study, where gene expression analysis in pancreatic islets from T1D patients showed not only up-regulation of genes involved in cell death, but significant inhibition of glucose transport as well 3 .…”
Section: Discussionsupporting
confidence: 91%
“…However, the genetic risk of T1D has only recently been analysed using genome-wide association studies, identifying over 60 T1D related susceptibility regions within the human genome, marked by single nucleotide polymorphisms 2 . This gene expression analysis revealed changes in genes related to inflammation (cytokines) and endoplasmic reticulum (ER) stress, leading to the activation of apoptosis 3 .…”
Section: Specific Gene Expression In Type 1 Diabetic Patients With Anmentioning
confidence: 99%
“…MCP3 is increased in serum of autoantibody-positive children [43] as well as in monocytes from patients with T1D [44] and individuals at risk for autoimmune diabetes [45]. Additionally, MCP1 and MCP3 are suggested to be involved in mouse models of autoimmune diabetes, particularly in infiltration of Th1 cells in the pancreas [46], and MCP1 was detected recently in the islets of Langerhans from a donor who recently developed T1D, but not a control donor [47], showing that MCPs may be involved actively in the development of T1D. The exact role of MCPs in development of autoimmune diabetes in general and virusinduced autoimmune responses in particular remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 is induced by IL-1β in the clonal 832/13 and INS-1E β-cell lines, two distinct rat insulinoma cell culture models, based on our unpublished microarray experiments [ 54 ]. In addition, CCL2 expression is increased in rat and human islets exposed to IL-1β [ 5 ] and in islets isolated from a human subject with T1DM [ 9 ]. The elevated expression of CCL2 in response to β-cell exposure to IL-1β requires the p65 subunit of NF-κB [ 5 ].…”
Section: Transcriptional Regulation Of Individual Chemokine Genes mentioning
confidence: 99%
“…Thus, the p65 subunit of NF-κB is the major transcription factor used to induce the expression of the CCL2 gene in pancreatic β-cells, leading to mRNA accumulation and secretion of CCL2 protein [ 5 ]. As proof of principle for inflammatory disease, elevated expression of CCL2 and other chemokines is observed in islets of NOD mice [ 10 ], hIAPP transgenic mice [ 57 , 58 ], obese mice [ 11 , 32 ], humans with T1DM [ 9 ], and humans with T2DM [ 12 ]. Notably, these are all situations where IL-1β levels are also enhanced.…”
Section: Transcriptional Regulation Of Individual Chemokine Genes mentioning
confidence: 99%